Effect of individualized positive end-expiratory pressure based on electrical impedance tomography guidance on pulmonary ventilation distribution in patients who receive abdominal thermal perfusion chemotherapy - Xiao, Li; Yu, Kang; Yang, Jiao-Jiao; Liu, Wen-Tao; Liu, Lei; Miao, Hui-Hui; Li, Tian-Zuo (Frontiers in Medicine, 2023)
Background: Electrical Impedance Tomography (EIT) has been shown to be useful in guiding individual positive end-expiratory pressure titration for patients with mechanical ventilation. However, the suitable PEEP level and whether the individualized PEEP need to be adjust during long-term surgery (> 6h) was not known. Meanwhile, the effect of individualized PEEP on the distribution of pulmonary ventilation in patients receiving abdominal thermoperfusion chemotherapy is unknown. The primary aim was to observe the effect of EIT-guided PEEP on the distribution of pulmonary ventilation in patients undergoing cytoreductive surgery (CRS) combined with hot intraperitoneal chemotherapy (HIPEC). Secondary aim was to analyzed for their effect on postoperative pulmonary complications. Methods: Forty-eight patients were selected and randomly divided into two groups, with 24 patients in each group. For control group (group A), PEEP was set as 5cmH2O, while in EIT group (group B), individual PEEP was titration and adjust every 2 h with EIT guided. Ventilation distribution, respiratory/circulation parameters and PPCs incidence were compared between the two groups. Results: The average individualized PEEP was 10.3 ± 1.5 cmH2O, 10.2 ± 1.6 cmH2O, 10.1 ± 1.8 cmH2O, and 9.7 ± 2.1 cmH2O at 5 minutes, 2 hours, 4 hours, and 6 hours after tracheal intubation during CRS + HIPEC. Individualized PEEP was correlated with ventilation distribution in region of interest (ROI)1 and ROI3 at 4 h mechanical ventilation, and ROI1 at 6 h mechanical ventilation. The ventilation distribution under individualized PEEP was back-shifted during 6 h, but moved to the ventral side under PEEP 5 cmH2O in control group. The respiratory and circulatory function indicators were both acceptable either under individualized PEEP or PEEP 5 cmH2O. The incidence of total PPCs was significantly lower under individualized PEEP (66.7%) than PEEP 5 cmH2O (37.5%) for patients with CRS + HIPEC. Conclusion: The appropriate individualized PEEP was stable at around 10cmH2O during 6 h for patients with CRS + HIPEC, along with better ventilation distribution and lower total PPCs incidence observed than fixed PEEP 5cmH2O.